A experiência do impossível: O problema da responsabilidade política em Jacques Derrida - Siscar, Marcos [UNESP] (My University, 2006)
This is intended to approach some aspects of the articulation between knowledge and social injunctions in order to understand the problems concerned with the determination of its finality by the very discourse. By analysing the controversy aroused by the work of Jacques Derrida, it can be noticed that the subordination of the discourse autonomy to the obligation of a response is based on the necessity of considering singular reasons; to actively recognize them would be one of the conditions for a rigorous reinterpretation of the discourse nature and role in the contemporary world.

O presente trabalho procura abordar alguns aspectos da articulação entre o conhecimento e as injunções de ordem social e política, esclarecendo os problemas que são colocados em jogo na determinação, pelo discurso crítico, de sua finalidade. Por meio das polêmicas surgidas com o trabalho de Jacques Derrida, notamos que o condicionamento da autonomia do discurso a um dever de resposta está fundado na necessidade de consideração de razões singulares; reconhecê-las de maneira ativa seria uma das condições para que, com o rigor necessário, o discursso reinterprete sua natureza e seu papel no mundo contemporâneo.
The experience of impossibility: Issue of political responsibility in Jacques Derrida
Keywords: Aesthetics; Criticism (philosophy and literature); Deconstruction; Jacques Derrida